Improving the Creative Character of Elementary School Students Through Tri Hita Karana Habituation - Hartayani, Ni Nyoman Putri; Wulandari, I Gusti Agung Ayu (Indonesian Values and Character Education Journal, 2022)
Lack of creative character generated by students in daily activities. In the learning process, students feel indifferent when the teacher provides a stimulus in the form of interesting objects, and students do not have the initiative to ask questions. In doing work, students tend to imitate their friends. This study aims to analyze the application of Tri Hita Karana habituation to improve students' creative character. This research is a classroom action research (CAR). This research is planned in several cycles, with three meetings. The subjects of this study were fifth-grade elementary school students. The data collection method used is the non-test method with the type of observation. The students' creative character data in this study were collected using observation sheets. The data analysis method used is the descriptive analysis technique. The research data shows that the average value of student character results in the first cycle is 63 (good category), and the average value of student character results in the second cycle is 85 (very good category). Based on the results of these studies, it can be concluded that applying Tri Hita Karana habituation in learning can improve students' creative character. This research implies that the results of this study can be used as a reference for improving students' character.